Adenoid Hypertrophy in Adults and Nasal Obstruction - Hamad, aKhalid D.; Alhamad, Raghdan M.D.; Jassim, aAnmar A. (AL-Kindy College Medical Journal, 2014)
Background .To know the incidence of adenoid hypertrophy in adults causing nasal obstruction and other nasal complains.Methods.Prospective studyof(140 ) adult patientstheir main chief complaint were nasal obstruction , presented to Otolaryngology department at Aljumhory Teaching Hospital in Mosul , from the period (september 2010 to september 2011) ,their age ranged from (21 to 53) years . They were investigated clinically, radiologicaly ,and nasal endoscopic examination was carried out (rigid and fibro-optic ) . Adenoidectomy was performed for those with adenoid hypertrophy and sent for histopathological study .Results:. we found adenoid enlargement in(24) patients (17.14%),in addition to nasalobstruction they were also complaining of Post nasal discharge (19) patients, followed by snoring (17) patients , headache and facial pain (15) patients, deafness and tinnitus (8) patients and other rhinologicalsymtoms. The patients were followed up for a period ranged from (4 -16) months. We found that (91.6%) were relieved of their nasal obstruction, (82.3%) were relieved from snoring .Other nasal symptoms ; post nasal discharge, headache and facial pain, sore throat and tonsillitis, deafness , tinnitus ,rhinorrhia, Rhinolaliaclausa, otalgia were improved in (68.4% - 50%).Conclusions:Nasal obstruction ,snoring ,post-nasal discharge ,and aural symptoms were often caused by adenoid enlargements in adults .Because the examination of the nasopharynx was inadequate ,many cases of enlarged adenoid were misdiagnosed. Adenoid enlargements in adults should always borne in mind as a cause of nasal obstruction and other rhinological symptoms. Nasal endoscopic examination including the nasopharynx should be done for proper diagnosis.